Associated Factors of the Need for Mechanical Ventilation Following Traumatic Injuries; a Registry-Based Study on 2,708 Cases in Iran - Ramezani, Zahra; Baigi, Vali; Zafarghandi, Mohammadreza; Rahimi-Movaghar, Vafa; Farahmand-Rad, Reza; Zolfaghari Sadrabad, Akram; Piri, Seyed-Mohammad; Hassan Zadeh Tabatabaei, Mahgol Sadat; Naghdi, Khatereh; Salamati, Payman (Archives of Academic Emergency Medicine, 2025)
Introduction: Traumatic injuries can affect respiration both directly and indirectly. This study aimed to evaluate the predictive factors of need for mechanical ventilation (MV) following traumatic injuries. Methods: This Retrospective registry-based cross-sectional study comprised trauma patients admitted to a major referral trauma center in Iran, from March 28, 2019, to January 31, 2023, identified within the National Trauma Registry of Iran (NTRI). Logistic regression analysis was used to assess the association between demographic and clinical variables with the need for MV. Results: A total of 2708 trauma patients with a mean age of 41.79 ± 21.84 (range:1-98) years were included (73.4% male). A total of 251 (9.3%) patients were admitted to the Intensive Care Unit (ICU); 113 (4.2%) experienced MV. The significant associated factors of need for MV based on the univariable analysis were age ≥ 65 years (p <0.001); penetrating trauma (p < 0.001) and falling (p = 0.01); private mode of transportation to ED (p < 0.001); site of injury (p < 0.001); heart rate ≥ 100/ minutes (p = 0.04); O2 saturation < 90 % on room air (p < 0.01); Glasgow Coma Scale (GCS) < 13 (p< 0.001); and injury Severity Score (ISS) ≥ 9 (p< 0.001). Based on the multivariate logistic regression analysis, the independent predictors of the need for MV in trauma patients were the site of injury (p < 0.001), GCS < 13 (p < 0.001), and ISS ≥ 9 (p < 0.001). Conclusion: Based on the findings, ISS ≥ 9, GCS < 13, and site of injury were among the independent predictors of the need for MV following trauma.